Keefektifan Model Pembelajaran Mind Mapping Terhadap Hasil Belajar Matematika Materi Bangun Ruang pada Siswa Kelas V SD Negeri 44 Cakranegara - Suharti Endang Pratiwi (Lembaga Bale Literasi, 2022)
The purpose of this study was to determine the effectiveness of the mind mapping model on learning outcomes in mathematics. The sample of this research is fifth grade students of SD Negeri 44 Cakranegara. The experimental design used in this study is the Nonequivalent Control Group Design. The technique of collecting data on learning outcomes uses multiple choice tests and descriptions. Data on learning outcomes were analyzed using the t-test, while to calculate the effectiveness of the mind mapping model in Mathematics subject on spatial use the N-Gain (normal gain) test. The results of the study show that the learning outcomes of those who use the mind mapping learning model are greater than the learning outcomes of students whose learning uses conventional methods. Based on the results of the data analysis above, the results obtained are r count = 0.992 and r table = 0.514. According to the formula, if r count > from r table, it is said that the variables x and y are correlated with a high correlation at 5% significance in the statistical distribution table. The independent variable x has a positive and significant effect on the variable y which is at the level of 0.80 ≤ r ≤ 1.00 and its placement has very high reliability. If rcount > r table, namely 0.992> 0.514, the instrument is declared valid and reliable with a significance of 5%. Likewise with the correlation significance test obtained t table = 1.753 and t count = 2.591, if t count > t table then it means that the alternative hypothesis is accepted.